2012
DOI: 10.1603/ec10373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant Combinations on Population Characteristics of <I>Bemisia tabaci</I> Biotypes B and Q

Abstract: In recent years, the dominant biotype of Bemisia tabaci (Gennadius) has shifted from biotype B to Q in many locations of China. Our field monitoring showed that B. tabaci biotype Q could be found on pepper Capsicum frutescens L. while biotype B could not be found on the plant. To study the role of the host plant in the displacement of biotype B by Q, the adult mortality, female fecundity, and adult emergence of both biotypes B and Q on different host combinations were studied using a model system involving pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Asia II 5 was only detected in two districts in central and northern Punjab, and Asia II 7 only in northern Punjab, but these are the first records for these species in Pakistan. Other studies have reported the rapid displacement of one whitefly species by another [29], [30], [81], [82]. For example, Guo et al [19] reported that MEAM 1 was dominant in most provinces of China prior to 2007, but that the Mediterranean (MED) species was now dominant species in at least 11 provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Asia II 5 was only detected in two districts in central and northern Punjab, and Asia II 7 only in northern Punjab, but these are the first records for these species in Pakistan. Other studies have reported the rapid displacement of one whitefly species by another [29], [30], [81], [82]. For example, Guo et al [19] reported that MEAM 1 was dominant in most provinces of China prior to 2007, but that the Mediterranean (MED) species was now dominant species in at least 11 provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al. () suggested that presence of non‐preferred plants might affect the population fitness. Moreover, other factors influence the results, such as the growth status of plants, the photoperiod, and even the interspacing of hosts in polyculture.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary laboratory experiments showed that pepper was not a preferred host for either biotype, when compared with eggplant. However, the negative impact of pepper on adult mortality, fecundity and survival was much greater for the B than the Q biotype (Chu et al ., 2012b). This result suggested the possibility that the Q biotype might be capable of adapting to a wider range of plant species, compared to the B biotype.…”
Section: Introductionmentioning
confidence: 99%